Analisis Prioritas Pengeluaran Pemerintah Dalam Mempengaruhi Perekonomian Indonesia Pasca Pandemi Covid-19 - Suyanto (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2021)
The background of this research is the government's efforts to carry out economic equality after the Covid-19 pandemic. This action was carried out as a step for the economic recovery of the people affected by the pandemic. Therefore a strategic analysis is needed to map priorities in government finance. The research method used in this research is descriptive with a qualitative approach. Data collection methods in this study are observation, interviews, and documentation studies. While the data analysis used in this study is data reduction, data presentation, and drawing conclusions. In accordance with the presentation of the results of this study, it shows that government spending is the funds used by the government to fund various projects and other expenditures in an effort to improve society as a whole. To maintain economic stability, the government's role in controlling economic flows is very important. As stated in the fifth precept, social justice for all Indonesian people, the impact of government spending on the Indonesian economy cannot be separated from Pancasila's assistance in helping stabilize the economy of all Indonesian people. the government's goal is to prevent socio-economic disparities among the population, government spending in Indonesia must be broad and evenly distributed across all levels of society. Since then, Pancasila must be practiced by the government to control spending. Keyword: Government spending, Priorities, Economy